The liability of foreignness in capital markets: Sources and remedies - Bell, R Greg; Filatotchev, Igor; Rasheed, Abdul A (Journal of International Business Studies, 2012)
The accelerating pace of global capital market integration has provided new opportunities for firms to raise capital abroad through global debt issues, cross-listings, and initial public offerings in foreign stock exchanges. However, existing empirical evidence suggests that foreign firms tend to be at a disadvantage compared with domestic firms, and they often suffer from investors’ “home bias”. The objective of this paper is to understand why firms are facing problems when accessing capital in foreign markets, and possible mechanisms that can help to mitigate these problems. It expands the liability of foreignness (LOF) research beyond the product market domain to include liabilities faced by firms attempting to secure resources in foreign capital markets. We identify key differences between product and capital markets related to information environment, time structure of transactions, and linkages between buyers and sellers. We analyze institutional distance, information asymmetry, unfamiliarity, and cultural differences as the main sources of capital market LOF (CMLOF). We suggest possible mechanisms that managers can employ to mitigate CMLOF and overcome investors’ “home bias”: bonding, signaling, organizational isomorphism, and reputational endorsements. We also outline directions for further theoretical and empirical development of the CMLOF research.